Complete guide to the CITP body of knowledge - Singleton, Tommie (AICPA : Wiley, 2011)
Looking for tools to help you prepare for the CITP Exam? The CITP self-study guide consists of an in-depth and comprehensive review of the fundamental dimensions of the CITP body of knowledge. This guide features various and updated concepts applicable to all accounting professionals who leverage Information Technology to effectively manage financial information. There are five dimensions covered in the guide: Dimension I Risk Assessment Dimension 2 Fraud Considerations Dimension 3 Internal Controls & Information Technology General Controls Dimension 4 Evaluate, Test and Report Dimension 5 Information Management and Business Intelligence The review guide is designed not only to assist in the candidate's preparation of the CITP examination but will also enhance your knowledge base in today's marketplace. Using the complete guide does not guarantee the candidate of successfully passing the CITP exam. This guide addresses most of the subjects on the CITP exam's content specification outline and is not meant to teach topics to the candidate for the first time. A significant amount of cooperating and independent readings will be necessary to prepare for the exam, regardless of whether the candidate completes the review course or not.